Psychology and Catholicism contested boundaries - Kugelmann, Robert, 1948- (Cambridge University Press, 2011)
"In this historical study of psychology and Catholicism, Kugelmann aims to provide clarity in an area filled with emotion and opinion. From the beginnings of modern psychology to the mid 1960s, this complicated relationship between science and religion is methodically investigated. Conflicts such as the contested boundary between psychology and the Church of 'person' versus 'soul' are debated thoroughly. Kugelmann goes on to examine topics such as the role of the subconscious in explaining spiritualism and miracles; psychoanalysis and the sacrament of confession; myth and symbol in psychology and religious experience; cognition and will in psychology and in religious life; humanistic psychology as a spiritual movement. This fascinating study will be of great interest to scholars and students of both psychology and religious studies but will also appeal to all of those who have an interest in the way modern science and traditional religion coexist in our ever-changing society"--